Inspiring respect for fathers as coparents through a trauma-informed, infant-family mental health transformation of community-based services: process and early implementation with a multi-agency community collaborative - McHale, James; Burton, Donna; Negrini, Lisa; Jacob, Alexandra Albizu; Butler, LaDonna (Frontiers in Psychology, 2023)
Introduction Despite compelling evidence that high-quality early care has an enduring impact, there has been little coordinated effort to transform services delivery to infuse Trauma-Informed Family Centered (TI-FC) principles into community-based agencies serving children and their families. A need for more culturally attuned, family-sensitive, evidence-based, and trauma-informed supports, especially for vulnerable children, their families and fathers, is apparent in evidence amassed by key stakeholders within the geographic area of this study. This report details the planning process, TI-FC training series, and organizational profile assessments. Authors conclude with recommendations regarding the establishment of multi-agency collectives, to include fathers, toward betterment of infant-family mental health at the community level. Methods The current case study details the community-level transformational effort in which major health, mental health, substance abuse, and child welfare organizations serving families of children age 0-3 worked collaboratively to enhance TI-FC services. We describe a four-stage process (1 - planning, 2 - assessment of organizational readiness, 3 - surveys, document reviews and focus groups, 4 - delivery of a training series) detailing the work of the collaborative, guided by key agency decision-makers. Results The study found significant initial success in adapting approaches to serving children 0-3 and their families through TI-FC perspectives. By proactively engaging several lead organizations in a deliberative planning process with universal aims and transformational principles, the collaborative team was able to coordinate organizational assessment, staff training and consultation, self-monitoring of organizational shifts, and problem-solving of obstacles and solutions to TI-FC services delivery. Discussion All agencies succeeded in completing comprehensive, multi-faceted analyses of organizational culture, preparing personnel for TI-FC services through comprehensive training, and utilizing this collaborative to make deliberate and customized changes within their programs, as concerns both support of families and father engagement. Preliminary data indicate that important shifts took hold and signified changes across key domains of TI-FC care.